How does Climate Technology Contribute to Economy? Empirical Evidence from Provinces in China - Zhang, Xinyue; Masron, Tajul Ariffin (International Journal of Economics and Financial Issues, 2024)
Existing study has extensively explored nexus between climate change on economy. However, effect of climate technology has received limited attention, which adjust relationship between climate and economy in various scenarios. Hence, this study examined Chinese provinces from east to west, incorporating impact of climate technology from 1997 to 2022 by ARDL model. The long-run results demonstrate significant role of climate technologies on economy in reducing drawbacks of climate. Moreover, negative influence of climate is moderated in middle and west provinces through climate technology. Policymaker concern to what extent climate technology affect desert environment and local economy in middle and western regions, providing incentives to make policy. These findings imply that climate technology is imperative to ensure long-term sustainable growth, need further promoted and widely applied.